Measuring Dyes Concentration Using a Low-Cost Visible-Light Spectrophotometer - Al-Sabbagh, Baseem; Abdulrazzaq, Nada N. (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
A low-cost, RGB LED-based visible-light spectrophotometer was designed to measure dyes concentration. Dyes are widely used as indicators or coloring agents in different applications and knowing their concentration is an essential part for many studies. The proposed spectrophotometer provides many functionalities that clones the traditional expensive spectrophotometers for a budged price under 50. It was aimed to provide a versatile tool for instructors and educators to teach their students the fundamental concepts behind spectrophotometry. Malachite green, methyl red, and methyl orange dyes were chosen to be good samples to show the integrity of the proposed spectrophotometer in terms of accuracy, repeatability, and sensitivity as compared to a conventional measurement.